Compensatory proteolytic responses to dietary proteinase inhibitors from Albizia lebbeck seeds in the helicoverpa armigera larvae - Hivrale, Vandana K.; Lomate, Purushottam R.; Basaiyye, Shriniwas S.; Kalve, Neeta D. (Arthropod-Plant Interactions, 2013)
Plant proteinase inhibitors (PIs) have been shown to reduce the growth rates in larvae of numerous insect species. On the other hand, insects can also regulate their proteinases against plant PIs. In the present study, we report the compensatory activities of Helicoverpa armigera (Hubner) (Lepidoptera: Noctuidae) gut proteinases against the PIs of Albizia lebbeck seeds. Total of ten proteinase inhibitor bands were detected in the seed extract of A. lebbeck. Bioassays were conducted by feeding H. armigera larvae on diet containing partially purified PIs from A. lebbeck seeds. Results show that larval growth and survival was significantly reduced by A. lebbeck PIs. We found that higher activity H. armigera gut proteinase (HGP) isoforms observed in the midgut of control larvae were inhibited in the midgut of larvae fed on test diet. Some HGP isoforms were induced in the larvae fed on PI containing test diet; however, these isoforms showed lower activity in the larvae fed on control diet. Aminopeptidase activities were significantly increased in the midgut of larvae fed on test diet. A population of susceptible and resistant enzymes was observed in the midgut of H. armigera, when fed on diet containing PIs from A. lebbeck seeds. Our initial observations indicate that H. armigera can regulate its digestive proteinase activity against non-host plant PIs, too. It is important to study the exact biochemical and molecular mechanisms underlying this phenomenon in order to develop PI-based insect control strategies.
Keywords: Albizia lebbeck; Helicoverpa armigera; Midgut proteinases; Proteinase inhibitors; regulation

Penicillin acylases revisited: importance beyond their industrial utility - Avinash, Vellore Sunder; Pundle, Archana Vishnu; Ramasamy, Sureshkumar; Suresh, Cheravakkattu Gopalan (Critical Reviews In Biotechnology, 2016)
It is of great importance to study the physiological roles of enzymes in nature; however, in some cases, it is not easily apparent. Penicillin acylases are pharmaceutically important enzymes that cleave the acyl side chains of penicillins, thus paving the way for production of newer semi-synthetic antibiotics. They are classified according to the type of penicillin (G or V) that they preferentially hydrolyze. Penicillin acylases are also used in the resolution of racemic mixtures and peptide synthesis. However, it is rather unfortunate that the focus on the use of penicillin acylases for industrial applications has stolen the spotlight from the study of the importance of these enzymes in natural metabolism. The penicillin acylases, so far characterized from different organisms, show differences in their structural nature and substrate spectrum. These enzymes are also closely related to the bacterial signalling phenomenon, quorum sensing, as detailed in this review. This review details studies on biochemical and structural characteristics of recently discovered penicillin acylases. We also attempt to organize the available insights into the possible in vivo role of penicillin acylases and related enzymes and emphasize the need to refocus research efforts in this direction.
Keywords: beta-lactam; choloyl glycine; in vivo role; Ntn hydrolases; pathogenicity; quorum sensing; regulation; signalling

Cellulase hyper-producing fungus penicillium janthinellum NCIM 1366 elaborates a wider array of proteins involved in transport and secretion, potentially enabling a diverse substrate range - Christopher, Meera; Sreeja-Raju, Athiraraj; Kooloth-Valappil, Prajeesh; Gokhale, Digambar Vitthal; Sukumaran, Rajeev K. (Bioenergy Research, 2023)
The efficient breakdown of lignocellulose requires the concerted activity of multiple enzymes. Previous studies on Penicillium janthinellum NCIM 1366 (PJ-1366) have revealed a more versatile repertoire of cellulases as compared to the hypercellulolytic strain Trichoderma reesei RUT-C30. Since a robust transport and secretion network is necessary to achieve proficient enzyme production, the transporters and extracellular proteins of PJ-1366 identified from its genome data were compared with those of Penicillium rolfsii (the phylogenetically closest species) and T. reesei RUT-C30 (the industrial work horse for cellulase production). Transmembrane proteins formed 20.4%, 21.0% and 18.2%, respectively of the proteome of PJ-1366, P. rolfsii and T. reesei RUT-C30, and 292 of them were mapped as transporters in PJ-1366. Major facilitator superfamily transporters (264) and sugar transporters (167) are abundant in PJ-1366, which probably aid in the uptake of oligosaccharide inducers of cellulase. The number of extracellular proteins (1007) in PJ-1366 is the highest reported for a Penicillium species. Also, PJ-1366 encoded 1.5 x more proteins involved in carbohydrate metabolism than the other fungi, and its secreted CAZymes belonged to much more diverse families (73), potentially enabling the fungus to act on heterogenous substrates. Structural differences in some untranslated protein response (UPR) effectors like Pdi and Clx detected in PJ-1366 may facilitate unique modes of cellulase regulation.
Keywords: Cellulase; Pathway; Penicillium; regulation; Secretion; Transport